MAKNA BACAAN SURAT-SURAT AL-QUR’AN DALAM TRADISI RUWATAN DESA SUKOLELO PRIGEN PASURUAN - Irfan; Wiwin Ainis Rohtih (Pascasarjana PAI Multikultural Universitas Yudharta Pasuruan, 2022)
Ruwatan is a cultural tradition left by ancestors since ancient times. This tradition has been preserved from generation to generation by its supporters with various motivations and goals that cannot be separated from the life view of the Javanese people in general. Tradition and culture have become flesh and blood in people's bodies wherever they are. So that when tradition and culture collaborate with a religion, finally the religious teachings themselves appear as things that are ingrained in a community. From the results of the research, the ruwatan process in the genting village was carried out by reading Yasin's letter which in certain verses was read several times. Ruwat In Junggo Hamlet, using letters that are read are letters at-taubah and additional special prayers. In the traditional Ruwat ceremony, Surat Yasin is also one of the most frequently read letters. Surat ar-Rahman, recently the letter ar-Rahman so that later will make his child get love from Allah SWT. While Surat al-Waqi'ah so that his sustenance is cheapened. Reading the letter at-taubah symbolizes the attitude of regret and repentance from children and families who carry out ruwat